Trying to Include but Supporting Exclusion Instead? Constructing the Roma in Slovak Educational Policies - Miškolci, Jozef; Kováčová, Lucia; Kubánová, Martina (European education, 2017)
Based on a social constructivist theoretical framework, this research study examines how the design of proinclusive educational policies and the general public construct the Roma students and parents in Slovakia. For this purpose, data from two selected educational policies and five focus groups conducted in five regions in Slovakia were analyzed. The findings demonstrate that the Roma are constructed negatively as irresponsible dependents and deviants not valuing education and incapable of making wise decisions about their lives. These findings can be considered relevant for policy formulation processes because proinclusive policies may sabotage their own goals if negative social constructions of a certain societal group are embedded in them.